CHAPTER FOUR CLAY MINERALS, DEEP CIRCULATION AND CLIMATE - Fagel N. (My University, 2007)
This chapter focuses on the clay minerals, deep circulation, and climate. Clay minerals are the main constituents of recent deep-sea or abyssal sediments. Their role as paleoclimatic and paleoceanographic indicators has been investigated by X-ray diffraction techniques. In marine sediments, clays are mainly detrital and their abundances provide abiotic proxy data, which may be used to decipher either (1) climate changes in the source area on adjacent landmasses, (2) changes in the intensity of the transport agent, or (3) changes in the ocean currents that disperse the terrigenous input. Clays are sensitive indicators of their environment of formation, and their composition may be used to constrain climatic variations which do not affect other size fractions. The composition of terrestrial clay mineral reflects the prevailing weathering regimes, which control the nature and intensity of pedogenetic processes in continental source areas. Weathering depends primarily on climate zonation, which determines the intensity of physical and/or chemical weathering. The chapter describes the relationships between (1) clay mineral abundance in deep-sea sediments and deep circulation and (2) clay variability and short- or long-term climate changes.